1992
DOI: 10.1002/ijc.2910500326
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐inhibitory effect of quercetin and presence of type‐II estrogen‐binding sites in human colon‐cancer cell lines and primary colorectal tumors

Abstract: We studied the effect of quercetin (Q) on the proliferation of HT-29, WiDr, COLO 201, and LS-174T human colon cancer cell lines. Q, between 10 nM and 10 microM, exerted a dose-dependent, reversible inhibition of cell proliferation. Cell-cycle analysis revealed that the growth-inhibitory effect of Q was due to a blocking action in the G0/G1 phase. Using a whole-cell assay with 17 beta-[3H]-estradiol as tracer, we demonstrated that all these cell lines contain type-II estrogen-binding sites (type-II EBS). By usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 22 publications
4
81
0
Order By: Relevance
“…Ginkgetin selectively inhibited the proliferation of human ovarian carcinoma cells OVCAR-3 via the induction of apoptosis in a dose dependent manner [12]. The function of flavonoids such as kaempferol and quercetin is mediated by interaction with type II estrogen receptors [13]. Kaempferol can be an estrogen agonist or growth inhibitor depending on its concentrations used.…”
Section: Introductionmentioning
confidence: 99%
“…Ginkgetin selectively inhibited the proliferation of human ovarian carcinoma cells OVCAR-3 via the induction of apoptosis in a dose dependent manner [12]. The function of flavonoids such as kaempferol and quercetin is mediated by interaction with type II estrogen receptors [13]. Kaempferol can be an estrogen agonist or growth inhibitor depending on its concentrations used.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin acts as an anti-proliferative agent by inhibiting cell proliferation, cell growth, and cessation of cell cycle of colon, breast, gastric, oral, prostate and ovarian cancer cells [104][105][106][107][108][109][110]. Studies on kaempferol are few but are contradictory as their proliferative/ anti-proliferative activity is based on its concentration.…”
Section: Dietary Fibersmentioning
confidence: 99%
“…Thus it behaves as an initiator in a two stage in vitro cell transformation model (Sakai et al, 1990) and potentiates the carcinogenic activity of azoxymethane in rats (Pereira et al, 1996), but it inhibits the action of TPA in mice (Kato et al, 1983) and causes cell growth arrest in a variety of tumour or established cell types (Hosokawa et al, 1990;Ranelletti et al, 1992;Scambia et al, 1993;Piantelli et al, 1995;Avila et al, 1994;Plaumann et al, 1996). Its cytostatic e ect has prompted the proposal that quercetin be used as an anticancer agent .…”
Section: Quercetin Inhibits Proliferation Of Palf Cellsmentioning
confidence: 99%
“…It has been shown that quercetin induces mutations in both prokaryotic and eukaryotic cells (Bjieldanes and Chang, 1977;Nakayasu et al, 1986), through the generation of DNA single-strand breaks (Rahaman et al, 1990;Fazal et al, 1990) and that it can substitute for DMBA in a two-stage cell transformation model (Sakai et al, 1990). In addition to its mutagenic properties, quercetin induces cell cycle arrest (Hosokawa et al, 1990;Ranelletti et al, 1992;Plaumann et al, 1996), disrupts normal cellular signalling pathways by interfering with kinases and phosphatases (Graziani et al, 1983;Van Wart-Hood et al, 1989;Matter et al, 1992) and induces protein degradation (Ahmed et al, 1994).…”
Section: Introductionmentioning
confidence: 99%